Adaptasi Pembelajaran Muatan Lokal Bahasa Jawa dalam Pelaksanaan Kurikulum Merdeka di Madrasah Ibtidaiyah: Abstrak - Khoiril Hidayah; Naila Alfa Khusna; Ulfa Alfia; Muhammad Fikri Abdun Nasir (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2023)
Abstract: Teachers often only use lectures to guide student learning during learning, the teacher delivers material, and students only listen. In addition, the only teaching materials that are often used are books that are used to support the process of learning Javanese, namely textbooks and student worksheets. When a teacher asks a question, the majority of students can only respond soberly and wait for responses from other students. The problem experienced by students at MI NU Nurus Shofa in learning Javanese is that they have not fully mastered Kromo Javanese because in their daily lives they still use Indonesian, as well as difficulties in writing, memorizing and reading Javanese script because students find it difficult. This shows that the involvement of students in learning is only passive. The purpose of this study was to examine how the Adaptation of Javanese Language Local Content Learning in the Implementation of the Independent Curriculum at Madrasah Ibtidaiyah. The research method used is descriptive qualitative with a descriptive or description approach. This qualitative descriptive approach is carried out by presenting facts obtained from data sources and interviews in the field. The results of the study show that developing Javanese knowledge, attitudes and skills in an effort to preserve Javanese culture for students. In planting, the learning activities in the classroom influence or have a good impact on students. Based on the observation that students are able to learn and remember Javanese language subjects. The implication of this research is that it can provide an understanding of learning Javanese local content in the implementation of the independent curriculum at Islamic elementary schools, so that it can contribute to student and school achievement.